Strength and anaerobic responses of elite young female sprint and distance runners - Thorland, W. G.; Johnson, G. O.; Cisar, C. J.; Housh, T. J.; Tharp, G. D. (Medicine & Science in Sports & Exercise, 1987)
Young female track runners (N = 31), at least half of whom were between 9 and 12 years of age, the remainder in the average age range of 14+ years, were classified as sprint (<= 400 m) or middle distance runners (up to 3,200 m). They were well-trained and of national junior level. They were tested on a Cybex II dynamometer for peak torque during leg extension, and on a Monarch bicycle ergometer to determine anaerobic power and capacity as revealed by the Wingate Anaerobic Test. Body composition was determined by underwater weighing. Results: Among physical characteristics, there was a relationship to age but not to event classification. Sprinters were no different to distance runners in stature. Fat-free weight was significantly related to performance measures. When other variables were corrected for fat-free weight variance, their associations with performance variables were reduced considerably. In terms of performance, older subjects were stronger at all Cybex II velocities. Event related differences only occurred at higher speeds (240 degrees per sec). Among anaerobic power values, only older athletes demonstrated substantially higher levels than the other subjects. There were no significant differences in anaerobic capacity. Implications: One would expect successful sprinters to be characterized by the ability to generate high levels of anaerobic power relative to some measure of body size. However, this study suggests that distinguishing characteristics only become evident in the upper age groups of competition. The final stages of maturation appear to separate out distinguishing physical capacities. Growth of fat-free weight and maturation appear to augment high proficiency (anaerobic power) in sprint events. Consequently, it is reasonable to assert that in younger performers the metabolic characteristics of either sprinting or distance runners are general and similar. Sport specific capabilities only appear at upper age levels. It would be wrong to predict sprint or distance capabilities from anaerobic measures taken on young children because at that age they do not predict any performance classification.